2001
DOI: 10.1042/bj3550509
|View full text |Cite
|
Sign up to set email alerts
|

cyp7b1 catalyses the 7α-hydroxylation of dehydroepiandrosterone and25-hydroxycholesterol in rat prostate

Abstract: Dehydroepiandrosterone (DHEA) is the most prominent circulating steroid in humans, and it is a precursor for sex-steroid synthesis in peripheral tissues, including the prostate. Recently, enzyme-mediated pre-receptor metabolism has been recognized as a key step in determining steroid action in vivo. Hydroxylation of 3β-steroids at the 7α-position has been reported in rat and human prostate to be a major inhibitory pathway to sex-steroid synthesis/action. However, the molecular identity of the enzyme responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Data from mouse studies indicate some fundamental interaction between PPARa and sex hormones. It has been shown in mice that PPARa is involved in estrogen signaling and reproduction (30)(31)(32). Conversely, female rats treated with testosterone and male rats treated with estrogen altered their mRNA concentration of PPARa (33).…”
Section: Discussionmentioning
confidence: 99%
“…Data from mouse studies indicate some fundamental interaction between PPARa and sex hormones. It has been shown in mice that PPARa is involved in estrogen signaling and reproduction (30)(31)(32). Conversely, female rats treated with testosterone and male rats treated with estrogen altered their mRNA concentration of PPARa (33).…”
Section: Discussionmentioning
confidence: 99%
“…Though most pronounced in rat and mouse liver, sex differences in CYP expression also occur in humans (16). A prominent member of the CYP superfamily, oxysterol 7α-hydroxylase (CYP7B1), is enriched in male compared with female liver (17)(18)(19)(20)(21). The CYP7B1 protein represses androgen biosynthesis by modulating the availability of dehydroepiandrosterone (DHEA), the main precursor of the male hormone testosterone (18).…”
Section: Introductionmentioning
confidence: 99%
“…A prominent member of the CYP superfamily, oxysterol 7α-hydroxylase (CYP7B1), is enriched in male compared with female liver (17)(18)(19)(20)(21). The CYP7B1 protein represses androgen biosynthesis by modulating the availability of dehydroepiandrosterone (DHEA), the main precursor of the male hormone testosterone (18). In contrast to its negative effect on androgen production, CYP7B1 promotes estrogen receptor (ER) activity by catalyzing the clearance of 27-hydroxycholesterol, which functions as a competitive ER antagonist (22).…”
Section: Introductionmentioning
confidence: 99%
“…Rose and coworkers (2001) also reported that expression of Cyp7b1 in the liver and kidney was greater in males compared with female mice. Little is known about the transcriptional regulation of Cyp7b1, however, this isoform contributes to bile acid synthesis through the 7␣-hydroxylation of 27-hydroxycholesterol (Schwarz et al, 1997;Martin et al, 2001;Memon et al, 2001). Because this isoform is important in cholesterol metabolism, it is interesting that a nonsignificant trend for a decrease in the levels of Cyp7b1 mRNA was observed in males with hyperinsulinemia and diabetes.…”
mentioning
confidence: 99%